The Impact of Technology on People's Behavior - Halimatussadiah, Siti; Yuni Lestari, Ria; Firdaus, Faisal; Fesly, Kelvin (Jurnal Primagraha, 2024)
This research aims to find out how digital public behavior and lifestyles in using digital media in society. The aspects examined in this research are convenience, consumptiveness, technological failure, and practicality in a digital society. This research uses a qualitative approach method. The qualitative descriptive research method in this research is a method that aims to explain or describe problems systematically, factually and accurately regarding the facts and characteristics of a particular population or area. The research results show that the development of digital technology has brought about major changes in social interactions and the way we communicate. Today's digital society is increasingly connected, with widespread access to information and social networks. However, there are also emerging challenges, such as privacy issues and anxiety related to social media use. Furthermore, this research concludes that a deep understanding of the impact of digital society needs to be developed, both for individuals and society at large, to ensure the healthy and productive use of digital technology.